2018
DOI: 10.1080/23320885.2018.1509717
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of a metacarpal head defect due to bite injury: two case reports

Abstract: We present two rare cases of acute osteomyelitis after bite injury that were reconstructed with a third metacarpal base osteoarticular flap and a vascularised medial femoral trochlea osteocartilaginous flap. The outcomes show that a vascularised osteoarticular flap is a good treatment option for a metacarpal head defect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 22 publications
0
5
0
3
Order By: Relevance
“…Small defects of the finger joints may be repaired with osteochondral plugs from the distal femur 19,20 or costal cartilage 19,21 . However, complete reconstruction of the metacarpal head and the use of an external fixator may be more advantageous, as evidenced by the increased range of motion and the lower DASH score than those reported by Nakanishi et al 18 …”
Section: Discussionmentioning
confidence: 99%
“…Small defects of the finger joints may be repaired with osteochondral plugs from the distal femur 19,20 or costal cartilage 19,21 . However, complete reconstruction of the metacarpal head and the use of an external fixator may be more advantageous, as evidenced by the increased range of motion and the lower DASH score than those reported by Nakanishi et al 18 …”
Section: Discussionmentioning
confidence: 99%
“…Apart from the aforementioned complications, the researchers also observed that out of the 13 joints, two exhibited lucency in the area of the phalangeal component, while one exhibited some degradation in the metacarpal component [99]. Subluxation of the unconstrained component was also reported by other researchers [100][101][102][103]. Like is the case with PIP joint surface replacement arthroplasty, MCP joint surface replacement arthroplasty has varying success rates since some patients are reported to experience dislocations of unconstrained implants.…”
Section: Mcp Joint Surface Replacementmentioning
confidence: 74%
“…Besondere Beachtung, auch im Hinblick auf Osteomyelitiden, sollten Menschen-und Tierbisse im Bereich der Hand bekommen. Speziell Katzenbissverletzungen, aufgrund der lanzettenartigen Zahnform mit möglicher schneller Eindringtiefe bis zum Knochen, und Hundebissverletzungen, aufgrund des oft erheblichen Riss-Quetsch-Gewebetraumas durch die starke Kraftentwicklung des Kiefers, stellen bei großer Verbreitung dieser Tiere ein besonderes Risiko dafür dar und werden häufig als Traumaursache beschrieben [2,[16][17][18][19]. Aber auch exotische Tiere finden zunehmende Verbreitung in der Tierhaltung und müssen in diese Überlegungen einbezogen werden [20].…”
Section: Posttraumatische Osteomyelitisunclassified
“…Diese ersten chirurgischen Maßnahmen der Infektsanierung müssen kompromisslos erfolgen und avital-entzündliches Gewebe gründlich entfernen, ohne die Keime zu verschleppen. Dabei [2,8,12,19,22,24,27,29].…”
Section: Operative Therapieunclassified
See 1 more Smart Citation